A novel proton exchange membrane fuel cell based power conversion system for telecom supply with genetic algorithm assisted intelligent interfacing converter. (15th March 2017) - Kaur, Rajvir; Krishnasamy, Vijayakumar; Muthusamy, Kaleeswari; Chinnamuthan, Periasamy
Graphical abstract: Highlights: Proton exchange membrane fuel cell based telecom tower supply is proposed. The use of diesel generator is eliminated and battery size is reduced. Boost converter based intelligent interfacing unit is implemented. The genetic algorithm assisted controller is proposed for effective interfacing. The controller is robust against input and output disturbance rejection. Abstract: This paper presents the fuel cell based simple electric energy conversion system for supplying the telecommunication towers to reduce the operation and maintenance cost of telecom companies. The telecom industry is at the boom and is penetrating deep into remote rural areas having unreliable or no grid supply. The telecom industry is getting heavily dependent on a diesel generator set and battery bank as a backup for continuously supplying a base transceiver station of telecom towers. This excessive usage of backup supply resulted in increased operational expenditure, the unreliability of power supply and had become a threat to the environment. A significant development and concern of clean energy sources, proton exchange membrane fuel cell based supply for base transceiver station is proposed with intelligent interfacing unit. The necessity of the battery bank capacity is significantly reduced as compared with the earlier solutions. Further, a simple closed loop and genetic algorithm assisted controller is proposed for intelligent interfacing unit which consists of power electronic boost converter for power conditioning. The proposed genetic algorithm assisted controller would ensure the tight voltage regulation at the DC distribution bus of the base transceiver station. Also, it will provide the robust performance of the base transceiver station under telecom load variation and proton exchange membrane fuel cell output voltage fluctuations. The complete electric energy conversion system along with telecom loads is simulated in MATLAB/Simulink platform and verified theoretically. The successful implementation and the obtained results illustrate the feasibility of the proposed system for reliable operation of the telecom towers.